Development of professional-pedagogical competence in future English language teachers - Turlybekov, Berdibay; Seidaliyeva, Guldana; Abiev, Bahytzhan; Kazyhankyzy, Lazura (International Journal of Innovative Research and Scientific Studies, 2024)
The study examines the professional pedagogical competence of future English language teachers. The concept of "professional pedagogical competence" is increasingly relevant in Kazakhstan’s higher education reform. It reflects teachers’ pivotal role and professional qualities in achieving high-quality education and upbringing. Our literature review defines the professional pedagogical competence of future English language teachers as an integrative set of qualities that indicate their personal and socio-moral experience. It also reflects their capacity to foster motivational, cognitive, and operational aspects within their professional domain. The outcomes of their pedagogical endeavors evidence this. Our model of professional pedagogical competence for future English language teachers is a pedagogical system that includes four blocks: target, conceptual, content-procedural, and criteria-evaluative. The criteria and indicators of professional-pedagogical competence are communicative, cognitive, operational-activity, and motivational-valuable. The communicative dimension emphasizes foreign languages as a means of personal and professional communication. The cognitive dimension emphasizes skills to solve non-standard lingua-pedagogical tasks. The operational-activity dimension reflects personality, professional development, and pedagogical activities. The motivational-valuable dimension emphasizes linguistic-cognitive motivation, professional self-awareness, the need for self-realization, and self-development. Our research findings contribute significantly to the discourse on teacher education in Kazakhstan. Our comprehensive model aligns with contemporary educational needs. It serves as a valuable guidepost for educational stakeholders and offers insights that can inform policy, curriculum development, and teacher training programs. Ultimately, it advances the overarching goal of enhancing the quality and impact of English language education in Kazakhstan.